THE ROLE OF LOGISTICS PERFORMANCE IN INCREASING MARKETING STRATEGY EFFECTIVENESS - Jamoliddinov Faxriyor Shodiyor o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article establishes logistics performance as a foundational driver of marketing strategy effectiveness in distribution. It argues that reliable delivery, inventory visibility, and supply chain agility are not just operational goals but critical marketing enablers. By ensuring promotional goods arrive on time and in full, logistics directly supports campaign success, retailer trust, and brand reputation. The article provides a framework for integrating logistics data into marketing planning, transforming the supply chain from a cost centre into a key source of competitive advantage and customer satisfaction.